SIKAP DAN PERILAKU MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KOTA MANADO - Robinson Pianaung (Jurnal Kesehatan Lingkungan, 2012)
Waste management basically requires active role of the community, especially in minimizing piles of waste, sorting waste, and making waste more useful. Waste problem at Manado Municipality based on the result of Basic Health Research is unavailability of waste disposal in the house (35.8%) and outside of the house (67.7%). To identify association between attitude and behavior of the community in managing waste at Manado Municipality; to identify large the association between the attitudes and behavior of the community in managing waste at Manado municipality. The study was an observational with cross sectional design and one moment measurement. Samples consisted of 216 responden selected through systematic random sampling technique. Data analysis used univariate, bivariate (product moment correlation). Attitude on waste management well enough (65.3%); and behavior on waste management well enough (60,6%). Score of product moment correlation coefficient (rxy) between and waste management was; attitude 0.507; and behavior 0.601 all with p<0.05. (1) There was correlation between attitude of the community and waste management at Manado municipality; and (2) there was correlation between behavior of the community and waste management at Manado municipality;